2019
DOI: 10.48550/arxiv.1911.02900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical investigations of the asymptotics of solutions to the evolutionary form of the constraints

Károly Csukás,
István Rácz

Abstract: A systematic investigation of the asymptotic behavior of near Schwarzschild vacuum initial data sets is carried out by making use of numerical solutions to the evolutionary form of the constraints. The decay rate of the monopole part of the trace of the tensorial projection of the extrinsic curvature is found to be of critical importance in controlling asymptotic flatness of initial data configurations.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…
In this paper we continue earlier investigations [10,12,19] of evolutionary formulations of the Einstein vacuum constraint equations originally introduced by Rácz. Motivated by the strong evidence from these works that the resulting vacuum initial data sets are generically not asymptotically flat we analyse the asymptotics of the solutions of a modified formulation by a combination of analytical and numerical techniques.
…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…
In this paper we continue earlier investigations [10,12,19] of evolutionary formulations of the Einstein vacuum constraint equations originally introduced by Rácz. Motivated by the strong evidence from these works that the resulting vacuum initial data sets are generically not asymptotically flat we analyse the asymptotics of the solutions of a modified formulation by a combination of analytical and numerical techniques.
…”
mentioning
confidence: 56%
“…With no control over the asymptotics it is therefore possible that the method generates initial data sets that lack a physical interpretation. Exactly this issue has been explored recently in [10,12,19]. It was confirmed that generic solutions of these equations are not asymptotically flat (this notion is defined in Section 4 below).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Restricting now attention to asymptotically flat configurations recall first that a threemetric h ij is asymptotically flat if in the asymptotic region it approaches the Euclidean metric not slower than ρ −1 . This condition, in virtue of the results in subsection 2.2.1 of [7], can also be rephrased in terms of the variables N , N A , γ AB by requiring them to fall off as…”
Section: Some Of the Global Aspectsmentioning
confidence: 99%